Lossless intra compression of point cloud geometry based on S3D coder using threads and block decomposition - Komatsu, Otho Teixeira (2024)
Dissertação (Mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2024.